PENGARUH FINANCIAL PERFORMANCE, FIRM SIZE, DAN TRANSFER PRICING TERHADAP PENGHINDARAN PAJAK - Tri Wirnarni, Rosa; Nurhayati, Nurhayati (Universitas Jakarta Internasional, 2025)
This study aims to analyze the effect of financial performance, firm size, and transfer pricing on tax avoidance. This study used 19 samples of mining companies in the energy sector listed on the Indonesia Stock Exchange (IDX) during 2019 - 2023 with a total of 95 observation data. In determining the research sample, the purposive sampling method was used, with path analysis processed using SmartPLS. The results of this study state that financial performance has no effect on tax avoidance. While firm size has an effect on tax avoidance. While transfer pricing has no effect on tax avoidance. Keywords: Financial Performance, Firm Size, Transfer Pricing, and tax avoidance